(STUDENTS’ KNOWLEDGE LEVEL OF BASIC LIFE SUPPORT (BLS) IN SCHOOLS KARTIKA 1-2 PRIVATE SENIOR HIGH SCHOOL MEDAN) - sagala, Piyanti Saurina Mahdalena (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
ABSTRACT Basic Life Support (BLS) is a crucial first aid measure in emergencies such as cardiac arrest and respiratory arrest. Lack of public knowledge, particularly among students, regarding basic life support (BLS) can result in delayed treatment, which can endanger the victim’s safety. This study aims to determine the level of student knowledge about basic life support (BLS) at Kartika 1-2 Private High School in Medan in 2026. The research used a descriptive method with a univariate approach. The population was all 48 ninth-grade science students, using a total sampling technique. Data collection was conducted using a questionnaire containing 20 multiple-choice questions. Data were analyzed descriptively in the form of frequency distributions and percentages. The results of the study showed that of the 48 respondents, the majority (28 respondents) had a good level of knowledge, 58.3% (28 respondents), a fair level of knowledge (12 respondents) (25.0%), and a poor level (8 respondents) (16.7%). This indicates that the majority of students already have a good understanding of basic life support (BLS), although some still need to improve their knowledge. The conclusion of this study is that students’ knowledge of basic life support (BLS) at Kartika 1-2 Private High School in Medan is considered good. It is recommended that educational institutions and healthcare professionals regularly improve basic life support (BLS) education and training to enhance student preparedness in emergency situations.